Species Composition and Stand Structure of Natural Forest in Hutan Pendidikan Gunung Walat, Sukabumi KOMPOSISI DAN STRUKTUR TEGAKAN HUTAN ALAM DI HUTAN PENDIDIKAN GUNUNG WALAT, SUKABUMI - Cecep Kusmana; Susi Susanti (Jurnal Silvikultur Tropika, 2015)
Natural regeneration is one of many factors which can change species composition and stand structure in Gunung Walat from time to time. The objective of this research is to analyze structure and species composition of vegetations on natural stand in Hutan Pendidikan Gunung Walat, Cibadak, Sukabumi. The location of observation determined by systematic sampling with random start method by using vegetation analysis plot on five strips. The research found 39 species of seedlings, 37 species of saplings, 22 species of poles, 23 species of trees and 21 species of understorey vegetation. Species composition in natural forest of HPGW is dominated by Tarenna fragrans and Bellucia axinanthera. Stand structure consists of stratum A, stratum B, stratum C and stratum E. Stratum A and B are dominated by species Maesopsis eminii while stratum C is dominated by Bellucia axinanthera and Schima wallichii. Stratum E is dominated by Selaginella wildenowii and Clidemia hirta. Tree density decrease exponentially from small diameter trees to large diameter trees which look like inverted J curve. This shows the sustainability of forest stand in the future will be secured.Keywords: natural forest, species composition, stand structure